Traditional Medicine and Healing Knowledge in the Context of Witchcraft: What Do the Holy Books and Religious Leaders Say? - Iwata, John Jackson (University of Dar es Salaam Library Journal, 2024)
In developing countries including Tanzania, traditional medicine and healing knowledge are increasingly utilised, and play a crucial role in healthcare. However, such knowledge often faces negative associations with witchcraft. This study explored perspectives from holy books and religious leaders regarding the management of traditional medicine and healing knowledge, the role of religion in the process, the potential efficacy of traditional healing knowledge for common health conditions, and the reasons behind the association with witchcraft. A mixed research approach was employed. Religious leaders formed the population of this study. Data were collected through semi-structured face-to-face interviews with religious leaders, supplemented with documentary review. Data from face-to-face interviews were qualitatively analysed through thematic content analysis before it was coded and analysed through SPSS for numeric descriptions. Results underscored the vital role of traditional medicine and healing knowledge in Tanzania ' s healthcare. Religious leaders and holy books recognised the necessity for managing such knowledge. Despite available religious texts describing traditional practices and their potential efficacy, religious leaders in the study area did not actively support the management of such knowledge, but rather associated it with witchcraft. The association with witchcraft arises from misunderstandings and societal biases introduced by foreign religions, early traders, and colonialists. The conclusion has been that although religious organisations played no role in the management of such knowledge, holy books, and religious leaders acknowledged the importance of doing that. Impoverishing, demonising, and disregarding were due to colonialism. The implications for managing knowledge in this context have also been provided.